PERANCANGAN MEDIA EDUKASI INTERAKTIF SELF-DISCLOSURE SEBAGAI UPAYA MEMINIMALISIR TERJADINYA MISUNDERSTANDING - Anhar, Jihan Maulidya Yocha; Prakarti, Vicia Dwi DB; Bermana, Ary Leo (Institut Seni Indonesia Padangpanjang, 2024)
Misunderstanding is at the root of several conflicts faced by adolescents. Errors in understanding messages when communicating make the communication process hampered so that adolescents have difficulty in establishing interpersonal relationships. Efforts to overcome this require interesting and effective creative teaching, one of which is by designing an educational media that can directly train understanding in communication for adolescents through self-disclosure. In Visual Communication Design science, designing creative educational media in an effort to do self-disclosure can be realized through designing board games.There are things that need to be considered so that the design of this work can be a solution according to the needs to be resolved. The process that must be carried out includes data collection through interview questionnaires, as well as analysis using 5W + 1H, so as to create a Board game design, Mascot, Logo, Standee and media mix from the We Card Talk board game design. The results obtained from designing self- disclosure educational media through the We Card Talk board game are interactive, solutive and attractive.